Use of modern educational technologies and standardization of control by the department of general dentistry of OMU IHU in order to improve the quality of training of dentists - Chulak, L. D.; Bas, A. O.; Bas, N. O.; Shuturmynsky, V. H. (Journal of Education, Health and Sport, 2017)
In the implementation of the strategy of Ukraine's integration into the European Union, one of the directions of the higher educational establishments in general and higher medical educational institutions in particular is the introduction of a system of integrated licensed examinations with a university-independent assessment of knowledge according to state standards. The results of the licensed exam allow you to get an objective picture of the level of theoretical training of graduate students, and the integral exam Krok-2 is a progressive form in the work of a higher medical school.The authors cover aspects of improving the educational process at the Department of General Dentistry. The implemented methods of teaching allowed to combine theoretical training of students for the practical training of their practical skills; made more interesting and clear independent non-auditing work of students; gave teachers the ability to control the quality of this work. It allows to improve the quality of preparation of students-dentists both for final examinations, and for the further professional activity.